2012
DOI: 10.1038/gene.2012.45
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β-associated miR-27a inhibits dendritic cell-mediated differentiation of Th1 and Th17 cells by TAB3, p38 MAPK, MAP2K4 and MAP2K7

Abstract: The alterations induced in dendritic cells (DCs) in the cancer microenvironment have not been extensively explored. We found that the tumor-associated factor TGF-b may selectively upregulate the expression of miR-27a via the SP1 transcription factor. Importantly, miR-27a altered the activity of NF-kB and MAPKs (mitogen-activated protein kinases) p38, JNK (c-Jun N-terminal kinases) and ERK (extracellular signal-regulated kinase 1/2). It influences the production of proinflammatory cytokines by targeting TAB3, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 49 publications
0
51
0
Order By: Relevance
“…In immune cells, such as monocytes/macrophages, plasmacytoid DCs, and myeloid DCs, IL-10 expression following TLR stimulation is dependent on ERK activation (35). Also, over-expression of miR-27a promotes the expression of IL-10 in human monocyte-derived DCs (36). Thus, we investigated the role of miR-27a in ERK activation in the monocytes exposed to alcohol and HCV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In immune cells, such as monocytes/macrophages, plasmacytoid DCs, and myeloid DCs, IL-10 expression following TLR stimulation is dependent on ERK activation (35). Also, over-expression of miR-27a promotes the expression of IL-10 in human monocyte-derived DCs (36). Thus, we investigated the role of miR-27a in ERK activation in the monocytes exposed to alcohol and HCV.…”
Section: Resultsmentioning
confidence: 99%
“…miR-27a targets multiple intracellular signaling networks (37). miR-27a has been shown to inhibit DC-mediated differentiation of Th1 and Th17 cells and promote the DC-mediated accumulation of Tr1 (CD4 + IL-10 + ), regulatory T cells, and increased secretion of IL-10 (36). A recent study has reported that miR-27a regulates the inflammatory response of macrophages by targeting IL-10 and decreasing the levels of IL-10 (46).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs post-transcriptionally control gene expression by targeting mRNAs for degradation or translational repression, and have multiple roles in various biological processes and diseases. Several miRNAs are found to be involved in the regulation of DC maturation and differentiation, such as miR-155 [105,106], miR-27 [107], miR-148/ 152a [108], miR-22 [109], miR-146a [110], etc. Recently, we established comprehensive miRNomes analysis in bone marrow HSCs, bone marrow-derived immature DCs, mature DCs and especially in the IL-10/NO-producing regulatory DCs.…”
Section: Epigenetic Control Of DC Tolerancementioning
confidence: 99%
“…For example, dendritic cell signaling via SP1 transcription factor–mediated increased expression of miR-27a can lead to altered NF-κ B and MAPK activity (74) (Figure 2, Panel C). As a result of the hampered cytokine signaling, increased levels of miR-27a led to decreased dendritic cell–mediated differentiation of Th1 and Th17 cells and increased tumor growth in vitro and in vivo (74). …”
Section: Introductionmentioning
confidence: 99%